53. MFF w Karlowych Warach - Góralik, Mikołaj Jakub (Apparatus. Film, Media and Digital Cultures of Central and Eastern Europe, 2018)
<span id="docs-internal-guid-eed37fef-7fff-3961-8f25-c84f49706a45" style="font-size: 11pt; font-family: Arial; color: #222222; background-color: #ffffff; font-weight: 400; font-style: normal; font-variant: normal; text-decoration: none; vertical-align: baseline; white-space: pre-wrap;">Mikołaj Jakub Góralik’s review of the 53d Karlovy Vary International Film Festival (29 June - 7 July, 2018)